Respostas

A melhor resposta!
2014-08-07T17:45:26-03:00
(3x - 2) + (x - 4)
3x - 2 + x - 4
4x - 6

===================

(5x - 1).(x + 3)
5x ^{2} + 15x - x - 3
5 x^{2} + 14x - 3

===================

( 2x^{3} y) ^{4}
 16x^{12}  y^{4}

===================

(5y + 4) ^{2}
25 y^{2}  + 40y + 16

===================

( x^{2} - 2x) - (3x - 5)
 x^{2} - 2x - 3x + 5
 x^{2} - 5x + 5

===================

(3a - b) ^{2}
9 a^{2} - 6ab +  b^{2}

===================

6a( a^{2}  - 2a + 7)
6 a^{3} - 12 a^{2} + 42a

===================

7xy - 9xy
-2xy
3 5 3